Assessing the viability of wood ash as a filler in asphalt mixtures - Wan Noor Hin, Mior Sani; Nur Shahirah, Shahrom; Rozalina, Ab Rashid; Norhidayah, Abdul Hassan; Al-Saffar, Zaid Hazim; Mohd Hazree, Hashim
Waste management is increasingly crucial worldwide, and integrating agro-waste into pavement construction offers a promising approach for sustainability and enhanced material properties. This research investigates the use of wood ash as a filler in asphalt mixtures, using varying proportions of 0%, 2%, 4%, and 6% replacement by weight of asphalt. Experimental tests, including softening point, penetration, Marshall stability and flow, indirect tensile strength, and abrasion loss, were conducted to assess the influence of wood ash on asphalt mixture properties. The findings reveal that wood ash can improve certain performance aspects such as stiffness and density at an optimal content of 4%, balancing tensile strength and flow properties. However, higher wood ash percentages negatively affected the mixture's overall durability and stability. These results underscore the importance of optimizing wood ash content to enhance asphalt performance. This study demonstrates that wood ash is a sustainable alternative to conventional fillers in asphalt production, contributing to environmental conservation and waste management. Further research is recommended to explore various aggregate gradations, binder types, and the potential of wood ash as an asphalt modifier for quality improvement. Such studies are vital for advancing pavement technology, improving infrastructure quality, and addressing environmental challenges.